Flavonoids from the aerial parts of Onobrychis montana subsp. scardica - Gođevac Dejan (Journal of the Serbian Chemical Society, 2008)
Rutin (1, main constituent) and two flavone C-glycosides, vitexin (2) and vitexin 2''-O-α-rhamnopyranoside (3) were isolated from the aerial parts of Onobrychis montana subsp. scardica. They were identified by 1H-NMR, 13C-NMR and UV-Vis spectroscopy (procedure with shift reagents), and high resolution ESI-MS. A relatively high content of 1 (5.27 mg/g of dry plant material), measured by HPLC, indicated O. montana subsp. scardica as a new natural source of this biologically active compound. The isolated flavonoid compounds might be of value as chemotaxonomic markers.